2022
DOI: 10.1002/smi.3122
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment experiences and emotion perception in young Chinese adults: Sex as a moderator

Abstract: Men and women seem to perceive and react differently to emotional stimuli and have different susceptibilities to childhood trauma. With a cross-sectional design, this study aimed to investigate whether specific patterns of childhood-maltreatment experiences are associated with specific patterns of emotion perception and the sex differences in this relationship. A total of 173 adults rated valence, arousal, and dominance for 60 pictures (varying in pleasantness, unpleasantness, and neutral emotion) from the Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Second, according to the desperation principle of conservation of resources theory, when abused adolescents' resources are exhausted, they enter a defensive mode to preserve themselves, which is often aggressive, such as more externalising problems (Hobfoll et al., 2018). Further, as suggested by the trauma coping model, exposure to childhood maltreatment can lead individuals to develop maladaptive schemas (such as the belief that others will hurt or abuse yourself or overfulfill the needs of others and neglect your own needs; Crawford & Wright, 2007), and negative cognitive processing tendency towards things, which were associated with internalising (Cui et al., 2011) and externalising problems (Calvete & Orue, 2012; Zhao & Wu, 2022). Lastly, complex posttraumatic stress disorder (CPTSD) construct may provide a valuable framework for understanding functional difficulties and forms of psychopathology frequently experienced by adolescents with childhood maltreatment histories.…”
Section: Discussionmentioning
confidence: 99%
“…Second, according to the desperation principle of conservation of resources theory, when abused adolescents' resources are exhausted, they enter a defensive mode to preserve themselves, which is often aggressive, such as more externalising problems (Hobfoll et al., 2018). Further, as suggested by the trauma coping model, exposure to childhood maltreatment can lead individuals to develop maladaptive schemas (such as the belief that others will hurt or abuse yourself or overfulfill the needs of others and neglect your own needs; Crawford & Wright, 2007), and negative cognitive processing tendency towards things, which were associated with internalising (Cui et al., 2011) and externalising problems (Calvete & Orue, 2012; Zhao & Wu, 2022). Lastly, complex posttraumatic stress disorder (CPTSD) construct may provide a valuable framework for understanding functional difficulties and forms of psychopathology frequently experienced by adolescents with childhood maltreatment histories.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to childhood adversity has been noticed as a risk factor of poor health outcomes, including both physical and mental health (Hustedde 2021 ; Petruccelli et al 2019 ; Sonu et al 2019 ). Studies also suggested that childhood trauma experience and its impact on outcomes may differ between genders (Xiao et al 2020 ; Yue et al 2023 ; Zhao and Wu 2022 ). Compared to general populations, BD patients usually have higher prevalence of childhood adversities, such as abuse, neglect, parenting absence, or familial economic difficulties (Bruni et al 2018 ; Miskowiak et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%